A study on factors that contribute low Muslim participant in buying life insurance market / Nurul Liyana Ramlan - Ramlan, Nurul Liyana (2011)
The objective of this study was to find out the factors that contribute low Muslim participant in buying life insurance market. This study was also conduced to identify the factors that contribute low Muslim participant in buying life insurance market, customer believe, not well informed on financial risk and intangible products. The purpose of this study was to determine the relationship between the factors that contribute low Muslim participant in buying life insurance market and the independent variables as well to find out the impact of low contribution of Muslim participant in buying life insurance. A questionnaire was used as the main instrument and the data was analyzed using SPSS version 18.0. The target population in this research is the customer in KPJ Healthcare ,Seremban Specialist Hospital. So mostly the questionnaire has been distribute at the hospital. From the distribution at KPJ Healthcare, Seremban Specialist Hospital, the researcher managed to collect 51 of 70 questionnaires. The finding shows that the independent variables which are customer believe, not well informed on financial risk and intangible products had strong relationship with the factors that contribute low Muslim participant in buying life insurance market.